The hydrogel containing a novel vesicle‐like soft crosslinker, a "trilayered" polymeric micelle, shows characteristic rheological properties. Issue 2 (5th October 2012) - Uchida, Yusuke; Fukuda, Kengo; Murakami, Yoshihiko
Abstract We have developed a novel hydrogel that is formed from a crosslinkable trilayered polymeric micelle and a polyamine for the sustained release of hydrophilic compounds. This hydrogel is quite unique because the vesicle‐like structure of the trilayered polymeric micelle acts as not only a crosslinker of the hydrogel but also a container of hydrophilic compounds. The hydrogel is rapidly formed by mixing both the trilayered polymeric micelle solution and the polyamine solution. The gelation property of the hydrogel, such as the storage modulus, can be changed by tuning the molecular weights, concentrations, and pH of the dissolving solvent of the hydrogel's constituent components. Furthermore, it is clarified that the structural difference among the micelles acting as crosslinkers affects the gelation property of the hydrogel. Amazingly, the hydrogel that is formed from the trilayered polymeric micelles possessing a vesicle‐like flexible structure exhibits a higher storage modulus than the hydrogel that is formed from the bilayered polymeric micelles possessing a highly packed, hard structure. Our results demonstrates that a microscopic structural difference of crosslinkers can induce a macroscopic (and, in some cases, an interesting and unexpected) change in the properties of the resulting hydrogels. For medical applications, the hydrogel proposed in the present article can encapsulate the hydrophilic compounds so that the hydrogel can be available as the material for their sustained release. © 2012 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2013